2020
DOI: 10.1101/2020.04.24.20075838
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vitamin D insufficiency is prevalent in severe COVID-19

Abstract: Background: COVID-19 is a major pandemic that has killed more than 196,000 people. The COVID-19 disease course is strikingly divergent. Approximately 80-85% of patients experience mild or no symptoms, while the remainder develop severe disease. The mechanisms underlying these divergent outcomes are unclear. Emerging health disparities data regarding African American and homeless populations suggest that vitamin D insufficiency (VDI) may be an underlying driver of COVID-19 severity. To better define the VDI-COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
142
0
11

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(172 citation statements)
references
References 31 publications
5
142
0
11
Order By: Relevance
“…Some preliminary studies have demonstrated that Vitamin D status and sun exposure are important factors to consider for reducing the rates of transmission, infection, and severity of illness. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…Some preliminary studies have demonstrated that Vitamin D status and sun exposure are important factors to consider for reducing the rates of transmission, infection, and severity of illness. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…Considering our knowledge on the role of vitamin D in modulating the immune system and in inhibiting a hyper activation of the inflammatory response, together with data from observational and clinical studies on vitamin D supplementation, various authors have also suggested a potential role of vitamin D in reducing the severity of the disease [ 183 , 184 , 185 , 186 , 187 ]. Vitamin D is especially known for its ability to reduce the “cytokine storm” that contributes to the pathogenesis of various viral infections, including COVID-19 [ 188 ].…”
Section: Vitamin Dmentioning
confidence: 99%
“…To date, we only have preliminary observations regarding the association of vitamin D deficiency and frequency and severity of COVID-19; the above mentioned study from Ilie and colleagues found a correlation between mean vitamin D levels in each country and COVID-19 cases and deaths [ 181 ]; D’Avolio and colleagues investigated vitamin D concentrations in a small cohort of 107 patients with a positive naso-pharyngeal swab for SARS-CoV2 in Switzerland, and found significantly lower vitamin D levels in patients than in controls with negative swabs [ 187 ]; Lau et al described a high frequency of vitamin D insufficiency (84.6%) in COVID-19 patients admitted to ICU in New Orleans, with a 100% frequency in patients younger than 75 years [ 188 ].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Observational studies have identified associations between suboptimal vitamin D levels and increased respiratory infection risk, including SARs-CoV2 infection (Alipio, 2020;Lau et al 2020), but do not Deficiency: <25 nmol/l (<10 ng/ml) Insufficiency: 25-50 nmol/l (10-20 ng/ml) Sufficiency: >50 nmol/l (>20 ng/ml) attribute causation. There is, however, pre-clinical data providing mechanistic evidence of how vitamin D impacts on risk for viral infections (Grant et al 2020).…”
Section: Mechanismmentioning
confidence: 99%